Efficacy of Bion, Amistar and Tilt in controlling brown spot and narrow brown spot of rice cv. BR11 (Mukta) (Journal of the Bangladesh Agricultural University, 2012)
Efficacy of Bion (benzothiodiazole), Amistar (azoxystrobin) and Tilt (propiconazole) was evaluated for controlling   Brown spot and Narrow brown spot of rice cv. BR11 (Mukta). Bion, Amistar and Tilt @ 50 mg/L, 1 ml/L and 1 ml/L,   respectively were sprayed at tillering and ear initiation stages that resulted in marked reduction of Brown spot and   Narrow brown spot. Bion, Amistar and Tilt significantly increased number of grains/ear and number of healthy   grains/ear by reducing number of diseased grains/ear. Bion, Amistar and Tilt resulted in 25.87, 32.17 and 26.76%   higher grain yield, respectively over the untreated control when sprayed at tillering stage.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.10986   J. Bangladesh Agril. Univ. 9(2): 201204, 2011